30º Encontros da Imagem: Génesis - Encontros da Imagem, Associação Cultural (UMinho Editora, 2020)
Coincidentally, the 30th edition of Encontros da Imagem - International Photography and Visual Arts Festival, will be celebrated in an odd time and of continuous uncertainty, in a very strange, different and difficult year, as a result of the Pandemic caused by Covid-19. The year 2020 will remain in everyone's memory as "the year of wearing the mask". Now, more than ever, we feel the responsibility for the role of cultural intervention that we have conquered over more than thirty years, in this sharing with the audiences that are interested in the current visual arts and in particular in photography. For this reason and concerning the respect that everyone deserves, again and again, we seek to overcome the difficulties and the numerous obstacles that we face, inherent to the present moment and thus carry forward, with due adjustments, the global project that we have outlined for this year's edition, whose main theme is Genesis. Similarly to the last two years and recovering a tradition from the late nineties, the thirty-six (36) exhibitions will be spread over twenty-three (23) spaces in the cities of Braga, Barcelos, Guimarães, Porto and Avintes (Vila Nova de Gaia), showing the works and projects of sixty-six (66) national and foreign photographers. Twenty years later, the project called Memories of the City is also incorporated. After addressing an invitation to the photographers from Braga, the brothers Hugo and Gonçalo Delgado, images were produced and fixed for future memory of moments and situations that marked the daily lives of the city, as a result of a confinement imposed by a Pandemic, which will forever define the year 2020. Supporting the idea of photography as a form of expression and artistic creation, alongside well-known names, other artists are also invited, which we consider equally important to the festival. As a result of an Open Call and the selection made by an international jury, works by young artists are also shown, which generally reflect avant-garde trends. It is true that the route is not long. But there are thirty-three years and thirty editions made. We crossed the most diverse paths of photography: historical, documentary and conceptual, contributing in a systematic and pedagogical way to a comprehensive vision of photography as a means of expression. However, it is long enough for us to be aware of having contributed positively to the development and qualitative growth of photography in Portugal.